Childhood Adversities and Depression in Adulthood: Current Findings and Future Directions. Issue 2 (23rd March 2017) - Liu, Richard T.
Abstract : Considerable support exists establishing a relationship between childhood adversities and adult depression. Consistent evidence has emerged linking early life adversities with a more chronic course for depression, as well as to poorer treatment outcomes. What remain decidedly less clear, however, are the moderators and mediating mechanisms underlying this association. This article provides a review of the existing research relating early adversities to adult depression, as well as recent studies suggestive of potential mediators and moderators of this relation. Advances in these areas are important for their potential to lead to the identification of new targets for clinical intervention for adults with a history of childhood adversities, as well as to the development of individually tailored prevention and treatment strategies.